The influence of organisational culture on a high commitment work system and organisational commitment : the case of a Chinese multinational corporation in South Africa - Mabuza, Linda Tengetile (Rhodes University, Faculty of Commerce, Department of Management, 2015)
Chinese presence in Africa has been rapidly increasing in the past few years and has been speculated to be mainly due to China seeking Africa's political alliance and access to Africa's natural resources and growing consumer markets. The growing presence of Chinese organisations in Africa, however, has not been without its challenges. In particular, Chinese multinational corporations (MNCs) in search of consumer markets in Africa have been cited as facing human resource (HR) challenges which may affect their organisational performance. In this regard, literature on human resource management has already established the important role of organisational culture, HR practices and organisational commitment in enabling organisations to achieve superior organisational performance. Given the fact that there is currently little research knowledge of Chinese presence in Africa at the organisational level, this research aimed to contribute empirical knowledge to the growing body of research in this area. Specifically, the main purpose of this research was to examine how the organisational culture of a Chinese MNC's South African subsidiary has shaped the nature of its high commitment work system (HCWS) and to assess the consequences thereof on organisational commitment. In alignment with the phenomenological paradigm, the research applied a descriptive and explanatory case study methodology in order to generate rich, qualitative data which was required for in-depth descriptions and to uncover the underlying interactions of the researched phenomena at the subsidiary. The selected case for the research was, therefore, a Chinese MNC operating in the personal computer (PC) industry, which had expanded its operations to South Africa in order to reach Africa's growing consumer markets. In particular, the South African subsidiary served as a PC sales and distribution organisation for the Chinese MNC. There were about 40 employees at the subsidiary who were all South African employees. Semi-structured, in-depth interviews were conducted with twelve employees from different job functions and across different job levels. Data collection was guided by the theoretical frameworks by Cameron and Freeman (1991) for organisational culture and Xiao and Bjorkman (2006) for the HCWS and organisational commitment. The data collected from interviews was then analysed through a qualitative, content analysis process. The findings of the research thus pointed to the market culture as the dominant organisational culture type at the South African subsidiary of the Chinese MNC; characteristics of the adhocracy and clan cultures were also discovered. The externally oriented market culture was found to be the most relevant for the high performance and market leadership aspirations of the subsidiary. The market culture also appears to be the most appropriate organisational culture that would enable the subsidiary to deal with the competitive nature of the PC industry. Furthermore, it was found that certain cultural values emphasised by the Confucian and Ubuntu value systems could have had a part to play in the formation of the subsidiary's organisational culture. The market culture was also found to have had the greatest influence in shaping the primarily performance oriented HCWS practices. Of the investigated HR practices at the subsidiary, all were found to be consistent with HCWS practices, with the exception of ownership practices and the performance appraisal system. Finally, although there were generally high levels of organisational commitment reported at the subsidiary, other job and organisational context factors besides the HCWS practices were found to be the major contributors to those feelings of organisational commitment. By investigating the organisational culture, HCWS and organisational commitment of a Chinese MNC in South Africa, this research has added to the body of knowledge concerning the growing presence of Chinese organisations in Africa. Based on the empirical findings of this study, several recommendations have been made in an attempt to assist the Chinese MNC manage the organisational commitment of its South African employees towards superior organisational performance.
Keywords: Corporate culture -- South Africa; Corporate culture -- Cross-cultural studies; International business enterprises -- South Africa; Investments, Chinese -- South Africa; Organizational commitment -- South Africa; Performance -- Management; Host countries (Business); Personnel management -- South Africa; South Africa -- Foreign economic relations -- China